If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(m+14)/3=8
We move all terms to the left:
(m+14)/3-(8)=0
We multiply all the terms by the denominator
(m+14)-8*3=0
We add all the numbers together, and all the variables
(m+14)-24=0
We get rid of parentheses
m+14-24=0
We add all the numbers together, and all the variables
m-10=0
We move all terms containing m to the left, all other terms to the right
m=10
| 5x-11=7x+21 | | -32-8n=-8(n+4) | | 3u+15=5(u-1) | | (v+44)/9=10 | | -11r+66r+44=44+10r | | 0.8w=0.48 | | 3x+13=-24 | | (p+35)/7=9 | | 3x-(4x+4)=4x-14 | | -16t^2+43t+4=0 | | -22+-6s=20 | | 11y-2=25 | | -35=-5/6v | | 11y=27 | | F(-5)=-2(3x+4)-9 | | 13+5h=78 | | -(8m+4)=4m-2(6m-+2) | | 6x-35-2x=17 | | (3/2)x=(189/20) | | 6v+3=57 | | 2-98(x)^-2=0 | | 2÷9g=-7÷9 | | -37+5x=7(2x-4) | | 28-6x=4=30-3x | | 9=108/x | | 2-98x^-2=0 | | 11y-5-3=25 | | g/7+82=91 | | 8a-8=8a-12 | | 3/2r-8=1/2r | | 2(m-7)=4(m+4)-18 | | |4(x+2)|+9=15 |